Hyperbaric Oxygen: A Lifesaver During COVID-19? - Shahzadi, Maria; Bilal, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Coronavirus (COVID-19) has become a worldwide pandemic after its emergence in late December 2019. The virus has evolved through mutations such as alpha, beta, gamma, delta, and epsilon variants. The one becoming variant, becomes precarious. COVID virus spiked a surge in hospitalizations and equipment utilization, as well as a scarcity of critical care resources. The precautionary measures, such as the use of masks and hand sanitizers, are advised to contain the virus.